Problematika Guru Dalam Menerapkan Penilaian Autentik Pada Kurikulum 2013 Di SD Negeri Bayan No. 216 Surakarta - Rohmani Dewi, Yayuk Nur; , Drs. Rubino Rubiyanto, M.Pd (2017)
This study aims to describe the pemahan authentic assessment against teachers, authentic assessment, application of its teachers in implementing the authentic assessment and teacher and principal efforts in overcoming problems in implementing teacher assessment authentic in SD Negeri Bayan No. 216 of Surakarta. This type of research is qualitative research design and research of Phenomenology. Interviewees from this research is the first grade teacher 1-5 Elementary school and the head of State of parrot No. 216 of Surakarta. Data collection techniques used are methods of structured interviews, observation and documentation. Techniques of examination of the validity of the data using the technique of triangulation of sources and methods. Technique of data analysis that is conducted during the study i.e. include the reduction of the data, the presentation of the data and the conclusion. The results showed that: 1) understanding teachers against this authentic assessment quite well, teachers use assessment instruments in accordance with curriculum guides in 2013. application of authentic assessment 2) the in SD Negeri Bayan No. 216 of Surakarta is already well underway, however some still constrained. 3) based on authentic assessment in applying the teacher that is complicated, time, circumstances students wholack support and use of the computer 4) Based upon the type of authentic assessment, namely the assessment of projects, performance assessment, and assessment ofjournal writing. 5) Effort teachers namely: question &answer with with colleagues, find information from other sources, following the development and workshop and training-training and exercise using a computer. The principal efforts as follows: understand the difficulties teachers, find examples of applications of valuation, find friends to explain, give the manual assessment provides supervision to the teacher and give evaluations to the teacher. Keywords: Teacher, Authentic Assessment, Curriculum 2013